The Effects of Educational Game-Based Learning through the Quizalize Website on the Development of Basic Mathematical Skills in Kindergarten 2 Children - ตั้งจิตสรรเสริญ, ศิญาภัสร์; สื่อเฉย, โศภิษฐ์; สุคลธ์, ศศิวิมล; บุญประกอบ, มนัส (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aimed to 1) study the development of basic mathematical skills of kindergarten 2 children who received learning experiences using educational games from the Quizalize website, and 2) compare the basic mathematical skills of kindergarten 2 children before and after receiving learning experiences using educational games from the Quizalize website. The data were collected from a sample group of 25 early childhood children in Kindergarten 2 at Sriboonyanussorn School, selected by Simple Random Sampling. The research instruments used were the experience plan using educational games and the basic mathematical skills test. The data were analyzed by finding the mean, standard deviation, relative development scores, and analyzing the differences in means using the t-test (Dependent Samples).          The results of the research found that 1) the early childhood children who received learning experiences using educational games from the Quizalize website had a relative development score of 35.08% overall, which was at the middle level of development, and 2) early childhood children who received learning experiences using educational games from the Quizalize website had higher scores on the basic mathematical skills test after the learning experiences than before the learning experience, with statistical significance at the .05 level.